A retrospective study of the incidence, clinical characteristics, identification, and antimicrobial susceptibility of bacteremic isolates of Acinetobacter ursingii. Issue 1 (December 2015) - Chiu, Chun-Hsiang; Lee, Yi-Tzu; Wang, Yung-Chih; Yin, Ti; Kuo, Shu-Chen; Yang, Ya-Sung; Chen, Te-Li; Lin, Jung-Chung; Wang, Fu-Der; Fung, Chang-Phone
Abstract Background Acinetobacter ursingii bacteremia is rarely reported. We investigated the incidence and clinical features ofA. ursingii bacteremia, performance of the identification system, and antimicrobial susceptibility of the isolates.Acinetobacter ursingii bacteremia patients were compared withA. baumannii bacteremia patients. Methods In this 9-year retrospective study, A. ursingii was identified using 16S rRNA and 16S–23S rRNA internal transcribed spacer sequence analysis. The performances of the Vitek 2, Phoenix, and matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) mass spectrometer systems for identifying isolates were tested. Pulsed-field gel electrophoresis (PFGE) was used to determine the clonality of the isolates. The minimal inhibitory concentrations of the antimicrobials were determined using the Vitek 2 system. Results Nineteen patients were identified.Acinetobacter ursingii was noted in 1.5–5.2 % of allAcinetobacter bacteremia cases. For the PFGE analysis, two isolates had smeared DNA, two had 93 % similarity, and 15 had similarity <80 %. Among 16 patients with complete medical records, 10 (62.5 %) had no identifiable source ofA. ursingii bacteremia. Most patients (n = 12) had underlying malignant disease. Patients withA. ursingii bacteremia had lower Acute Physiology and Chronic Health Evaluation II scores than those withA. baumannii bacteremia (median [interquartile range], 17.1 [10.0–24.7] vs. 24.9 [14.6–35.1]). Patients withA. ursingii bacteremia were also less likely admitted to the intensive care unit than patients withA. baumannii bacteremia (18.8 % vs 63.5 %, p value < 0.01). About half of the patients withA. ursingii (50.8 %) andA. baumannii bacteremia (62.5 %) had received inappropriate antimicrobial therapy within 48 h after bacteremia onset. However, patients withA. ursingii bacteremia had significantly lower 14-day (6.25 % vs 29.8 %, p value = 0.04) and 28-day mortality rates (6.25 % vs 37.3 %, p value = 0.02) than patients withA. baumannii bacteremia. Nine isolates (47.4 %) were correctly identified asA. ursingii and the other 10 isolates (52.6 %) were incorrectly identified asA. lwoffii by the Vitek 2 system. The Phoenix system incorrectly identified all 19 isolates. The MALDI-TOF mass spectrometer system correctly identified all 19 isolates. All theA. ursingii isolates were resistant or showed intermediate susceptibility to ceftriaxone and ceftazidime, but were susceptible to levofloxacin and imipenem. Conclusions Acinetobacter ursingii is a rare pathogen that mostly caused primary bacteremia in patients with malignancies. Patients withA. ursingii bacteremia had significantly lower disease severity and mortality rates than patients withA. baumannii bacteremia.